Things I never told you [large type] - Vogt, Beth K. (Vogt, Beth K. Thatcher Sisters novel., 2018)
"Ten years ago Payton Thatcher's twin sister died in an accident, leaving the entire family to cope in whatever ways they could. When her sister Jillian receives a frightening health diagnosis while planning her wedding, old wounds are reopened. Facing the possibility of another tragedy, the family must decide to pull together or be driven further apart"--